Two new species of Periphloea Redtenbacher, 1906 (Insecta: Phasmatodea: Pseudophasmatidae) from the Brazilian Amazon Basin - Heleodoro, Raphael Aquino; de Queiroz, Larissa Lima; Rafael, José Albertino (Zootaxa, 2021)
Two new species of Periphloea Redtenbacher are described based on female specimens from the Brazilian Amazon Basin, namely: P. amazonica sp. nov. (from North of Manaus, ZF-2 reserve, State of Amazonas, Brazil) and P. paraensis sp. nov. (from Eldorado dos Carajás, State of Pará, Brazil). The new species are compared to the other three species (all known from females) and a map of geographical records of the genus is provided, as well as an identification key to females of Periphloea.